Quantum overlapping tomography based on linear optics - Yang, Zhengning (Nanyang Technological University, 2023)
Quantum information science and technology is experiencing rapid development. The process raises an emerging demand for experiments to implement and demonstrate novel ideas to overcome the challenges towards the further application of quantum information. Linear optical systems have long been the most available and efficient platform for the demonstration of quantum information methods and concepts due to its robustness against the influence of environment. However, the large-scale multi-qubit linear optical information systems have long been suffering the low generated efficiency of the single photon sources, leading to a limited availability and scalability. In recent years, novel techniques such as beam-like SPDC open up new possibilities to break this bottleneck and further develop linear optical quantum information systems.